Formuły grzecznościowe z semantycznym komponentem sakralnym w języku mieszkańców wsi Zelena (Ukraina - huculszczyzna) = Terms of politeness with a?Semantic Sacral Component in the Language of the Inhabitants of Zelena Village (Ukraine - hutsulshchyna) - Sieradzki, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article studies the terms of politeness encountered in the Zelena village in the Hutsul Country (Ukraine). The set of polite phrases appearing in this area is treated by the author of the article as a closed collection constituting an important element of the politeness author of the article as a closed collection constituti model realized in specific social-cultural conditions.
Keywords: formuły grzecznościowe; "sacrum" w formułach grzecznościowych; Huculszczyzna; Zelena; politeness terms; "sacrum" in politeness terms; Hutsuls